Efektivitas Penggunaan Media Jaringan Berbasis Aplikasi pada Pembelajaran PAI di Era Digital - Parulian Sibuea; Aldi Maulana Ong; Darma Syahputra Hasibuan; Desi Sabtina; Filia Bunga Syahbrina; Nadirah Nadirah; Widya Gustriana; Wirda Aini Rambe (Transformasi Manageria: Journal of Islamic Education Management, 2024)
In this era, technology has been very advanced and developed to facilitate the process of education and learning, various kinds of technological media that we can find in this sophisticated era, one of which is very popular media and all humans can access it, namely network media. Network media has many features, one of which is application-based network media, with the use of interesting learning applications so as to provide attraction for educators, students. The method used by researchers in this study uses qualitative research methods with data collection techniques, namely observation and using tests to strengthen the research conducted. This study was carried out within 2 days by applying the use of network-based media in the classroom. This study aims to determine the effectiveness of using application-based network media in learning Islamic Religious Education.